Nanoflake-constructed porous Na3V2(PO4)3/C hierarchical microspheres as a bicontinuous cathode for sodium-ion batteries applications. (June 2019) - Cao, Xinxin; Pan, Anqiang; Yin, Bo; Fang, Guozhao; Wang, Yaping; Kong, Xiangzhong; Zhu, Ting; Zhou, Jiang; Cao, Guozhong; Liang, Shuquan
Abstract: Sodium-ion batteries (SIBs) have attracted considerable attention for large-scale energy storage systems as a promising alternative to lithium-ion batteries (LIBs) due to the huge availability and low-cost. Yet the development of SIBs has been hindered by the low reversibility, sluggish ion diffusion, as well as large volume variations. Herein, we report an efficient hydrothermal method for fabricating hierarchical porous Na3 V2 (PO4 )3 /C (NVP/C) microspheres assembled from interconnected nanoflakes. The NVP nanocrystals are uniformly wrapped by N-doped carbon layer. As a half-cell cathode, the NVP/C porous microspheres exhibit superior rate capability (99.3 mA h g −1 at 100 C) and excellent cyclic stability (79.1% capacity retention over 10, 000 cycles at 20 C). A full-cell configuration coupled with NVP/C cathode and SnS/C fibers anode exhibits an estimated practical energy density of 223 W h kg −1 . The superior performance can be ascribed to the hierarchical porous micro/nano structure along with N-doped carbon encapsulation, which provide bicontinuous electron/ion pathways, large electrode-electrolyte contact area, as well as robust structural integrity. This work provides a promising approach for boosting the electrochemical performance of battery materials via the integration of hierarchical structure and heteroatoms doped carbon coating. Graphical abstract: Image 1 Highlights: Nanoflake-constructed porous NVP hierarchical microspheres accompanied with a N-doped carbon coating were synthesized via a facile and controllable strategy. The effects of hydrothermal reaction time and concentrations of precursor solution on the micro/nano structure of the products are studied systematically and the morphological evolution mechanism is proposed. As for half-cell cathode, NVP/C porous microspheres exhibit outstanding high-rate and ultralong-life performance. An advanced sodium-ion full-cell based on the NVP/C-MSs cathode and SnS/C fibers anode delivers a practical estimated energy density of 223 W h kg -1 and long-term cyclability.